Identification of the Application of Vegetation Elements in the Biophilic and Comfort Concept in the Lobby, Dining Room & Public Space of Greenhost Hotel, Prawirotaman, Yogyakarta - Achmad, Fathi Khalidi; Rukayah, Siti (The Eastasouth Journal of Information System and Computer Science, 2024)
The abstract says, In modern cities, the built environment becomes oppressive; Urban spaces are almost unlivable in fact in cities more and more blighted due to design fads and industrialist buildings. Biophilic Design can reduce stress, increase creativity, clarity of thought and improve our well-being, and speed healing. The priorities of Biophilic Architecture are Natural Patterns in Space, Natural Analogy Patterns, and Natural Space Patterns. Yogyakarta has a large number of visitors attending the tourism sector in the Patrioman area, visitors often look for places such as accommodation, cafes, restaurants, and entertainment centers of socialize and relax to create significant business opportunities. Research objectives, some of the results of research that have been carried out with the Biophilic concept are taken, the aim of the research is as an alternative solution to create a healing environment by optimizing architectural design concepts to respond to the health, cognitive, psychosocial and psychological health of hotel users. The impression of this building is extensive on spatial vegetation by arranging the placement of mass, treating the space and mass of space with hiqh quality towards the natural environment, and using materials both inside and out as well as an appearance with a natural appearance to create positive response. This research hopes to be implemented in Greenhost Yogyakarta with a biophilic standardization of spaces in Greenhost Yogyakarta is mostly the application of the Biophilic design model which has been recommended by the fourteen Biophilic design models.